AI POWER SMART EXAM INVIGILATION USING ESP-32 CAM - Porf. Soni Mankari; Nitesh; Swati; Vaishnavi Dhotre; Vaishnavi Lade (International Educational Journal of Science and Engineering, 2026)
The ESP32-CAM based AI-powered smart exam invigilation system is an advanced solution designed to improve security, fairness, and monitoring during examinations. Traditional exam invigilation methods require continuous human supervision and may lead to errors, malpractice, and increased workload. This system uses the ESP32-CAM module along with Artificial Intelligence (AI) techniques to automatically monitor students during exams in real time. The camera captures live video streams and detects suspicious activities such as mobile phone usage, multiple faces, head movement, cheating behavior, or absence from the seat. The collected data can be processed using machine learning and computer vision algorithms to generate alerts and maintain exam integrity.